Deception of ambient temperature does not elicit performance benefits during a 5 km run in hot, humid conditions - Hanson, N. J.; Carriveau, D. M.; Morgan, H. E.; Smith, A. R.; Michael, T. J.; Miller, M. G. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was to investigate the effect of deception of ambient temperature on 5 km performance in recreational runners. Eleven participants (6 men, 5 women) each performed three 5 km runs in a random order consisting of a control trial (CON) in temperate conditions (21° C, 43% RH), a hot humid trial (HOT; 31° C, 65% RH) and a deception trial (DEC; 31° C, 65% RH), where participants were told it was 5° C lower than it actually was. Overall completion time was recorded at the end of trials; thermal sensation (TS), rating of perceived exertion (RPE), and core temperature (TC) were recorded each kilometer. Participants completed the 5 km run faster in the CON condition (23:18 ± 2:05; mean ± SD) compared with DEC (p = 0.005) and HOT (p = 0.014). There was no difference in completion time (p = 0.554) between DEC (25:11 ± 2:41) and HOT (24:25 ± 2:47). Similarly, TS was lower in the CON condition (5.7 ± 0.2) compared with DEC and HOT (p < 0.001 and p = 0.016, respectively) and no differences were seen between the DEC (6.4 ± 0.2) and HOT (6.5 ± 0.2) conditions. No differences in RPE (p = 0.115) or rise in TC (p = 0.289) were seen between the 3 conditions. Deception of the environmental conditions did not positively affect 5 km running performance, and no differences were seen in physiological or psychological variables.